Ratiocination over Deliberations in the Fiction of Trio- Anita Desai, Ruth Prawar Jhabvala and Nergis Dalal with special velleity towards relational complexity and ethnocentric intricacy - Sharma, Dr. Jaya (The journal of contemporary issues in business and government, 2021)
This paper attempts to analyze how the trio Anita Desai, Ruth Prawar Jhabvala and Nergis Dalal etch fragile human relationship in the wake of contemporary maladies creeping in the society. Attenuated emotional bonds, urge for more space, patriarchal subjugation, rifts in understanding eclipse conjugal harmony and nuptial relations. The trio has chosen to give voice to entangled man-woman relations, incompatibility in marriages, cultural ethnocentrism resulting in marital disharmony, alienation, estrangement, East-west Encounter, Identity Crisis, Familial nuances, Pseudo modernism in Indian society, social life and marital dissonance and feministic seclusion. Draught of female manifestations in Indian English Literature culminates with the foray of Anita Desai, Ruth Jhabwala, Kamla Markandey, Sudha Murthy, Jhumpa Lahiri, Chitra Bannerjee, Kiran Desai, Nergis Dalal etc. who dribbled it with the clear stream of their expressions. The initiation of female authors enlarged the dimension by giving voice to untold miseries, unheard experiences and unwritten encounters. Disparate streams of the works of the three contemporary writers Nergis Dalal, Anita Desai and Ruth Jhabwala sometimes sparkle with the streak of same themes manifested in different style.